A randomised controlled trial to compare the occurrence of postoperative nausea and vomiting in early versus conventional feeding in children undergoing daycare surgery under general anaesthesia - Ranju Singh; H Santoshkumar Huligeri; Pooja Singh (Indian Journal of Anaesthesia)
Background and Aims: The time paediatric patients should resume oral intake after surgery is still ill-defined. No specific evidence suggests that the usual practice of postoperative fasting of 4–6 h to reduce postoperative nausea and vomiting (PONV) is beneficial. The primary objective of this study was to assess the occurrence of PONV with early oral feeding compared to conventional feeding in children undergoing daycare surgery under general anaesthesia. Methods: A randomised controlled trial was conducted in 300 children undergoing daycare surgery under general anaesthesia. Children were randomised into the early feeding group (Group EF, n = 150) or the conventional feeding group (Group CF, n = 150). Group EF received carbohydrate-containing oral fluids when the child demanded feed in the postoperative period. Group CF received oral fluids 4 h post-anaesthesia. All patients were monitored for occurrence of PONV, postoperative pain, duration of hospital stay and parental satisfaction. The incidence of PONV was compared using the Chi-squared test, while other continuous variables were compared using the Student’s t-test. Results: Both groups were comparable regarding PONV (12% in Group EF vs. 18.7% in Group CF, P = 0.109). The Face, Legs, Activity, Cry, Consolability scores were significantly lower in Group EF at 0 min (P = 0.011), 30 min (P = 0.001) and 1 h (P < 0.001). Patients in Group EF had a significantly shorter duration of hospital stay, that is, 6.31 [standard deviation (SD): 3.52] [95% confidence interval (CI): 1.45–12.24] h in EF versus 10.13 (SD: 2.99) (95% CI: 5.12–16.33) h in CF (P < 0.001). Parents of the children in Group EF had significantly better parental satisfaction scores (P < 0.001). Conclusion: Early postoperative feeding in children undergoing lower abdominal, non-gastrointestinal surgery under general anaesthesia does not increase the incidence of PONV.